The spleen contributes importantly to myocardial infarct exacerbation during post-ischemic reperfusion in mice via signaling between cardiac HMGB1 and splenic RAGE - Tian, Yikui (Basic Res Cardiol, 2016)
The spleen plays a critical role in post-infarct myocardial remodeling. However, the role of the spleen in exacerbating myocardial infarction (MI) during acute ischemia/reperfusion (I/R) injury is unknown. The present study tests the hypothesis that splenic leukocytes are activated by substances released from ischemic myocardium to subsequently exacerbate myocardial injury during reperfusion. The left coronary artery in C57BL/6 mice underwent various durations of occlusion followed by 60 minutes of reperfusion (denoted as min/min of I/R) with or without splenectomy prior to I/R injury. Splenectomy significantly decreased myocardial infarct size (IS) in 40′/60′ and 50′/60′ groups (p<0.05); however, it had no effect on IS in 10′/60′, 20′/60′ and 30′/60′ groups (p=NS). In the 20′/60′ group, infusion of 40-minute ischemic heart homogenate (40-IHH) upon reperfusion increased IS by >3-fold versus infusion of 10-IHH (p<0.05). Splenectomy abolished the infarct exacerbating effect of 40-IHH, which was restored by splenic leukocyte adoptive transfer (SPAT). Furthermore, depletion of HMGB1 in the 40-IHH group abolished its infarct exacerbating effect (p<0.05), and 40-IHH failed to increase IS in both RAGE(−/−) mice and splenectomized wild-type mice with SPAT from RAGE(−/−) mice. The injection of 40-IHH significantly increased formyl peptide receptor 1 (FPR1) expression in sham spleens when compared to 10-IHH-treated sham & control mice. cFLFLF, a specific FPR1 antagonist, reduced myocardial neutrophil infiltration and abrogated the infarct exacerbating effect of 40-IHH during reperfusion. CONCLUSIONS: A cardio (HMGB1) – splenic (RAGE receptor) signaling axis exists and contributes to myocardial infarct exacerbation during reperfusion after prolonged ischemic insults by activating splenic leukocytes. The FPR1 is a potential therapeutic target for inhibiting the cardio-splenic axis that augments infarct size during post-ischemic reperfusion.